Technology firm value: The role of intellectual capital, enterprise risk management, and sustainability reporting - Anura, Dhea; Fahruna, Yulyanti; Azazi, Anwar; Malini, Helma; Syahputri, Anggraini (Junal Ilmu Manajemen, 2025)
This study examines the impact of intellectual capital, enterprise risk management, and sustainability reporting on the value of technology firms listed on the Indonesia Stock Exchange. Furthermore, this study investigates the moderating effect of profitability on the relationships above. A purposive sampling technique was employed to select a sample of 20 technology companies. Secondary data was collected from 2021 to 2023, yielding 60 observations. Moderated regression analysis (MRA) within a panel data framework was adopted for data analysis in this study. The research findings indicate that only intellectual capital exhibits significant positive associations with firm value. Conversely, enterprise risk management and sustainability reporting do not substantially influence firm value. Profitability could not moderate the relationships between intellectual capital, sustainability reporting, and firm value. Nevertheless, it moderated the relationship between enterprise risk management and firm value. The implications of these findings are expected to enrich both the theoretical and practical knowledge of firm value.